2021
DOI: 10.1016/j.ultsonch.2021.105627
|View full text |Cite
|
Sign up to set email alerts
|

Study on the influence of advanced treatment processes on the surface properties of polylactic acid for a bio-based circular economy for plastics

Abstract: Graphical abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 77 publications
(74 reference statements)
2
8
0
Order By: Relevance
“…Recent works have reported the degradation of polymeric plastics using the microbial approach [350][351][352][353]. Sourkouni et al [354] proposed that the activated oxidation process and biotechnology can boost the circular economy for plastics, in which bacteria and enzymes can digest plastics. During the process of end-of-life waste management, plastic wastes are discharged into the environment accidentally due to human error, transportation, and runoff.…”
Section: Recyclingmentioning
confidence: 99%
“…Recent works have reported the degradation of polymeric plastics using the microbial approach [350][351][352][353]. Sourkouni et al [354] proposed that the activated oxidation process and biotechnology can boost the circular economy for plastics, in which bacteria and enzymes can digest plastics. During the process of end-of-life waste management, plastic wastes are discharged into the environment accidentally due to human error, transportation, and runoff.…”
Section: Recyclingmentioning
confidence: 99%
“…Regarding the composites, the development of a general circular business model is necessary, but also quality protocols concerning end-of-waste criteria of each individual mix of materials are needed. We consider the field of the reuse of composite components or, in the best case, of the whole composite material as very important as a basis for the production of novel materials using biotechnological methods in combination with surface activation methods, such as high-power ultrasounds, UV, and atmospheric plasma [68][69][70]. Furthermore, socioeconomic pressure for the development of sustainable composite recycling solutions will accelerate the replacement and/or alter the waste-management handling of these materials by banning landfilling options to reduce environmental impacts in the framework of the circular…”
Section: Discussionmentioning
confidence: 99%
“…Recently, we have shown that the surface chemistry and composition of PLA is improved towards bacterial degradation (Sourkouni et al 2021 ; Kalogirou et al 2022 ). Several other studies have shown that photodegradation yields positive effects on the biodegradation of polymers by deteriorating the polymer surface and increasing the surface availability for biodegradation (Yang et al 2005 ; Longieras et al 2007 ; Jeon and Kim 2013 ; Vimala and Mathew 2016 ).…”
Section: Introductionmentioning
confidence: 99%